Pb and Zn in Peru: Supply trend and resource amounts - Acosta Ale, Jorge Gilberto (2016)
Until 2014, 14 million tonnes of Pb (metal based) and 41 million tonnes of Zn (metal based) were produced in Peru. Representative two Pb-Zn metallogenic belts were known in Peru. They are lower Cretaceous-Paleocene VMS Cu-Zn-Au metallogenic belt and Miocene epithermal, skarn, replacement & polymetallic vein metallogenic belt. If four new mining projects were launched and additional three mining projects were prepared until 2017, it seems possible to produce 0.34 million tonnes of Pb and 1.5 million tonnes of Zn additionally. In Pb-Zn metallogenic belt in Peru, potential Zn amounts range from 9 to 6000 million tonnes with 0.1 to 14% Zn and potential Pb amounts range from 5 to 2800 million tonnes with 0.04 to 5.3% Pb.